(untitled) (Fiep Bulletin - online, 2011)
The present studying had as an objective draw the motor profile of students from seven to eight years old, coming from the private teaching net in Macapá city. Made part of the sample 162 pupils, being 81 males and 81 females. The instrument used to collect the datas was the motor development scale (MDS), proposed by Francisco Rosa Neto (2002), that permit the verification of the motor age, having this like an indicative of the motor development where the children belongs to. After the realization of the tests we observed that the majority of the students were classified as medium normal (58%). The elements evaluated: the thin motriciy, the global motricity, the equilibrium, the corpore scheme, the space organization and the tempo organization demonstrated that the students are into of the normal parameters indicated by the protocol, suggesting the difference in some variable by sex. It was taken the student T test, to reassure these differences and the results reassured that the general motor age is superior to the chronological age for all the categories of age and sex analyzed. Among of the students of seven years old it was confirmed a difference statistically significant between boys and girls in global motricity and corporeo scheme, while among the students of eight years old the difference was reassured at the equilibrium variable. The investigation supplied us a general view of the motor profile of the researched pupils, and even so the knowledge about the evolutive stagium of a child. We hope that the results of this research can contribute for the improvement of planning and pedagogic actions of professionals that deal with children and also can promote knowledge supplying subside for new studying.